Feed enrichment with different oil sources on the growth and survival rate of Asian redtail catfish larvae (Hemibagrus nemurus) - Parma, Jesika Nadiyah; Aryani, Netti; Nuraini, Nuraini (Acta Aquatica: Aquatic Sciences Journal, 2025)
Asian redtail catfish (Hemibagrus nemurus) is one of the freshwater fish commodities with high economic value and already cultivated in Riau Province. Food that is given does not fully all the nutrition needed for larvae growth. One way to improve the feed quality is to enrich it with fish oil. This study aimed to determine the best oil sources in feed on the growth and survival rate of larvae. This research was conducted from August to September 2023 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine Science, University of Riau. This study used the experimental method of Completely Randomized Design (CRD) with 5 treatments and 3 replicates. The treatments used were P1 (commercial feed,) P2 (shark oil 8%), P3 (pangasius catfish 8%), P4 (squid oil 8%), and P5(cod liver oil 8%). Larvae were reared for 40 days with a stocking density of 5 individuals/L. The result of the research showed that enrichment feed with different oil sources had a significant effect (P<0,05) on the growth of absolute weight, absolute length, specific growth rate, and survival rate. Enrichment of feed with squid oil results the higher growth than the other treatments with absolute weight of 0,71 g, absolute length of 3,06 cm, specific growth rate of 14,03%/day, and survival rate of 68,00%. Larvae’s response to feeding was very aggressive and nothing was left. Water quality parameters during the study were still in the good category for Asian redtail catfish with temperatures 28,7-30,1°C, pH 6,5-6,8 and dissolved oxygen 4,0-5,3 mg/l. Keywords: Asian Redtail Catfish Larvae; Enrichment food; Growth; Survival rate